2022
DOI: 10.1111/ced.15144
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase‐4 inhibitor‐associated cutaneous eruptions: a retrospective observational study

Abstract: Summary Background Dipeptidyl peptidase (DPP)‐4 plays a complex role in immune regulation and its inhibition can have effects on the pathogenesis of various skin diseases. Studies have shown that DPP‐4 inhibitors are associated with an increased risk of bullous pemphigoid (BP). Aim To analyse the clinical and histopathological features of cutaneous adverse events in patients on DPP‐4 inhibitors. Methods We performed a retrospective review of patients with suspected DPP‐4 inhibitor‐associated cutaneous adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Authors found that vildagliptin could also have immunomodulatory functions via regulating IL‐6 production in DBP pathogenesis [54]. It is speculated that suppression of DPP‐4/CD26 may be involved in the disruption of BP180, major BP autoantigen, immunotolerance, and the subsequent development of epitopes for BP autoantibodies [55].…”
Section: Effects Of Dpp‐4 Inhibitors In Therapy Beyond Glucose Controlmentioning
confidence: 99%
“…Authors found that vildagliptin could also have immunomodulatory functions via regulating IL‐6 production in DBP pathogenesis [54]. It is speculated that suppression of DPP‐4/CD26 may be involved in the disruption of BP180, major BP autoantigen, immunotolerance, and the subsequent development of epitopes for BP autoantibodies [55].…”
Section: Effects Of Dpp‐4 Inhibitors In Therapy Beyond Glucose Controlmentioning
confidence: 99%